The European Court of Justice and its political impact. Issue 4 (4th July 2017) - Blauberger, Michael; Schmidt, Susanne K.
Abstract: This article reviews recent advances in the study of the European Court of Justice (ECJ) and its political impact at the European and member state levels. New quantitative as well as qualitative analyses show with great empirical precision that member state preferences guide the Court. The article summarises these findings, but argues that greater attention needs to be given to the (over-)constitutionalisation of EU law in order to fully capture the political impact of ECJ jurisprudence. Even if European judges are less activist than is often assumed and individual decisions are more restrained in the face of member state opposition, incrementally, case law evolves in a highly expansive fashion. And, exercising caution regarding unrealistic expectations about quasi-deterministic judicial law-making, it is found that the Court's constitutionalised jurisprudence impacts heavily on European and member state policy-making.